Lower-limb passive heat maintenance combined with pre-cooling improves repeated sprint ability - Beaven, C.; Kilduff, L. P.; Cook, C, J. (Frontiers in Physiology, 2018)
Pre-conditioning strategies to potentiate performance are a common feature of pre-competition routines. The elevation of muscle temperature is seen as a vital component of preparing for physical performance, while pre-cooling strategies have been adopted to offset fatigue during repeated efforts. We investigated the individual and combined effects of a passive heat maintenance strategy and the ingestion of an ice-water slurry on repeated sprint performance. In a random cross-over design, 12 professional male athletes performed 5 × 40 m maximal running sprints under one of four conditions following a standardized warm-up: 15-min passive rest (Control); wearing a lower-body survival garment (HEAT); consuming a 500 mL ice slushy (COLD); or wearing the survival garment and consuming the slushy (H+C). Measures of sprint speed, fatigue, heart rate, and rectal temperature were collected. Compared to COLD: HEAT improved Sprint 1 (ES: 0.84; p = 0.05), but negatively impacted Sprint 4 (ES: -0.87; p = 0.08), and Sprint 5 (ES: -1.57; p = 0.002). H+C was faster than Control for every sprint (ES: 0.28 to 0.66), clearly faster than COLD on Sprints 1-3 (ES: 0.73 to 0.54), and clearly faster than HEAT on Sprints 4 and 5 (ES: 1.31 and 1.87). Fatigue was greatest after the HEAT intervention with a large correlation between fatigue and rectal temperature (r = 0.66; p = 0.0204). While there are undoubtedly peripheral effects of cooling and heating on various aspects of muscle function and fatigue, understanding the integration of psychophysiological homeostatic feedback loops relating to a combined warming and cooling intervention may benefit sports in which repeat sprints are performed.